1928
DOI: 10.1007/bf01828330
|View full text |Cite
|
Sign up to set email alerts
|

Zur physikalischen Chemie der Hautoberfläche

Abstract: Auf der Inn sbrncker Tagung der Gese]lscha~t Deutscher Naturforscher und J~rzte (1924) hat der eine yon uns einen Referatvortrag fiber die physikalisehe Chemie der Haut gehalten. Es gait, einen ganz allgemeinen Einbliek in die physieo-ehemisehen Arbeitsweisen zu verbinden mit der Berficksiehtigung j ener speziellen Arbeitsresultate, die ffir die Erforsehung der Haut eine besondere Bedeutung besitzen. Sehon damals wurde auf die physieo-ehemisehe Eigenart der Vorggnge, welehe sieh auf der Oberflgehe der Haut abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
1

Year Published

1932
1932
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(21 citation statements)
references
References 6 publications
0
20
0
1
Order By: Relevance
“…The endogenous concentrations of UCA in human skin, calculated considering the mean thickness of the epidermis, extend over the range 0.5-8.9 mM (Laihia et al, 1998). It is plausible that these concentrations have an effect on maintaining the innate antibacterial, antiproliferative, and anti-inflammatory environment in the epidermal layer of human skin (''acid mantle''; Schade and Marchionini, 1928).…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous concentrations of UCA in human skin, calculated considering the mean thickness of the epidermis, extend over the range 0.5-8.9 mM (Laihia et al, 1998). It is plausible that these concentrations have an effect on maintaining the innate antibacterial, antiproliferative, and anti-inflammatory environment in the epidermal layer of human skin (''acid mantle''; Schade and Marchionini, 1928).…”
Section: Introductionmentioning
confidence: 99%
“…The term 'acid mantle' derives from an early publication of Schade [5]. Our working definition of skin pH was pH as measured by a flat glass electrode on the skin surface with a hydrated skin electrode interfaced.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the ecosystem of the resi dent human skin flora is largely resistant to outside factors: bathing once a day for 3 weeks or avoidance of washing of the forearms for the same length of time did not lead to either an overgrowth of transient, or a major shift in the composition of resident micro-organisms [10]. Yet these studies have been performed without looking at the pH value.…”
Section: Skin Ph and Bacterial Floramentioning
confidence: 98%
“…The concept of defense against micro-organisms due to skin surface acidity was first elaborated in some detail in the twenties and thirties by Marchionini and Hausknecht 19] and Schade and Marchionini [10]. This concept, termed the 'acid mantle concept', has long been a subject of contro versy.…”
Section: Skin Ph and Bacterial Floramentioning
confidence: 99%